Repasse cambial no Brasil: assimetrias setoriais, regionais e nas fases inflacionárias - Mendes, Samoel de Sousa (2022)
A considerable concern of monetary authorities is the evolution of price indices, since this phenomenon causes distortions in the markets. In addition to eroding the real values of wages, contributing to a greater concentration of income. There are several economic theories that explain the inflationary dynamics and which factors influence it, Phillips' work, for example, demonstrates the inverse relationship between the unemployment level and the price index. One of these factors is the influence of the exchange rate on price indices, which is usually called Pass-Through, or transfer of exchange rate movements to the price index. This work intends to contribute to the theme, estimating the exchange rate Pass-Through in inflation measured by the IPCA and its groups. For this, linear and nonlinear models with threshold effect of the Phillips curve with exchange rate are used, to verify if there is asymmetry of the effect of the exchange rate on inflation in regimes of higher and lower inflation. This analysis is performed for data at the monthly frequency in the period 2000.1 to 2019.7 for inflation measured by the IPCA and its groups: food, communication, personal expenses, residence, clothing, education, transport, health and housing. Among the results, it can be seen that in most inflation measures, the exchange rate effect is greater and significant only in the regime of higher inflation. Furthermore, the dynamics and intensity of this effect is different for inflation measured by the IPCA and among its subcategories.